Pattern of Metastases of Squamous Cell Carcinoma in Cervical Lymph Node with Occult Primary - Rashid, Mohammad Harun Or; Sattar, Md Abdus; Kabir, Abm Luthful; Haque, Md Anamul; Pramanik, Dhiman; Ali, Md Asgar (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To determine the pattern of metastesis of squamous cell carcinoma in cervical lymph node. Methods: This was an observational cross sectional study which was carried out in the departments of Otolaryngology and Head-Neck surgery of Bangabondhu Sheikh Mujib Medical University and Dhaka Medical College Hospital during the period of July 2012 to March 2013. A Total 30 patients were selected according to selection criteria and level of involved lymph node and nodal staging was determined by careful clinical examination, biopsy of all suspicious site, CT scan, MRI, USG and X-ray. Results: In this study majority of patients were within 40-80 years and most of patients were male. Maximum lymph nodes were 3-6 cm in size.90% cases were unilateral.50% cases were involved in level-II and most of cases (46.68%) were in stage N2. Conclusion:Metastetic squamous cell carcinoma in cervical lymph node of occult primary common in elderly patient and most of were male and involved the lymph node level II. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 66-70